(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
The research aims at evaluating in-vitro antimicrobial effects of methanolic leaf extract of Carissa edulis. The leaf of Carissa edulis was collected air-dried, ground to powder and extracted with methanol by cold extraction method to give a percentage yield of 28.03% w/w. The crude extract was defatted with n-hexane and partitioned with chloroform, n-butanol and water to give a percentage yield of 36.04%, 11.24%, 15.94% and 3.08% respectively. The extract fractions exhibited considerable amount of inhibition against almost all the test micro-organisms except for the n-hexane extract which had no activity. The activity of n-butanol extract (500 mg/ml), chloroform extract (500 mg/ml) and aqueous extract (500 mg/ml) was superior to the standard drug (Gentamacin) used. The MIC and MBC against the tested organisms ranged from 25 mg/ml to 50 mg/ml and 50 mg/ml to 100 mg/ml respectively. The results obtained from this study revealed that the leaf extract of Carissa edulis possesses antibacterial activity against some pathogenic microorganisms such as Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa and Staphylococcus aureus.